Graphic Design & Postmodernity - Cauduro, Flávio V. (2008)
This article presents a brief summay on the origins of the modernist aesthetics in the visual arts and in graphic design in order to sketch, afterwards, a short historical account of postmodern design. It is pointed out then that there is a recurrent postmodern design style which exploits a visual aesthetic which resembles that of palimpsests, for it uses several overlapping, transparent layers of heterogeneous signs in its layouts. The goal of that style seems to be to draw the viewer into a hermeneutic game of unlimited possibilities of interpretation which precludes the possibility of “easy” readings.